"It brought my family more together": Mixed‐methods study of low‐income U.S. mothers during the pandemic. Issue 3 (19th April 2022) - Haskett, Mary E.; Hall, Jodi K.; Finster, Heather P.; Owens, Caitlyn; Buccelli, Alexandra R.
Abstract: Objective: We sought to understand challenges and positive experiences of low‐income families during the pandemic. Background: Strength‐based perspectives of economically disadvantaged mothers are missing from literature on the impact of the COVID‐19 pandemic. Although it is imperative to recognize disparities that were highlighted by the pandemic, strengths‐based approaches and a resilience framework can help professionals build upon and learn from ways families manage during those times. Method: We used a mixed‐method approach to gain understanding of the unique experiences of 15 low‐income mothers at the height of the pandemic. We administered a brief COVID‐19 stress screener, the Five‐Minute Speech Sample measure, and an open‐ended question about potential positive experiences during the pandemic. Results: We learned that strength and resilience supersede the liabilities brought on by COVID‐19 that are so often focused on. We found highly divergent experiences across mothers in terms of stress; even mothers with high levels of stress readily identified positive aspects of life during the pandemic. Mothers' responses were indicative of greater feelings of warmth and tenderness than negativity about their children. Conclusion and Implications: We discuss findings in terms of strengths‐based practices and policies for mothers receiving public assistance and provide suggestions for continued research on resilience of mothers during the pandemic.